2005
DOI: 10.7863/jum.2005.24.7.985
|View full text |Cite
|
Sign up to set email alerts
|

Vibrography During Tumor Neurosurgery

Abstract: These findings indicate that vibrography is a feasible imaging method for brain tumor surgery and may have numerous potential applications in neurosurgery if further improvements are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…In this Letter, we report for the first time to our knowledge the recovery of the elastic property (though qualitatively) using photoacoustic imaging. This imaging of elastic property is promising for preclinical study and clinical applications of diagnosis and therapeutic treatment of diseases that are characterized by changes in the elastic property of tissues such as brain tumors [5], breast and prostate cancers [6], and Alzheimers [7] and subsequently, this study enhances the horizon of potential clinical applications of PA imaging to diagnosis and therapeutic treatments. On the other hand, the existing imaging modalities (ultrasound and MRI) for recovery of elastic property fail to give physiological information while PA imaging, as a single imaging unit, can provide multiple functional and structural parameters that are of great clinical interest and value.…”
mentioning
confidence: 86%
“…In this Letter, we report for the first time to our knowledge the recovery of the elastic property (though qualitatively) using photoacoustic imaging. This imaging of elastic property is promising for preclinical study and clinical applications of diagnosis and therapeutic treatment of diseases that are characterized by changes in the elastic property of tissues such as brain tumors [5], breast and prostate cancers [6], and Alzheimers [7] and subsequently, this study enhances the horizon of potential clinical applications of PA imaging to diagnosis and therapeutic treatments. On the other hand, the existing imaging modalities (ultrasound and MRI) for recovery of elastic property fail to give physiological information while PA imaging, as a single imaging unit, can provide multiple functional and structural parameters that are of great clinical interest and value.…”
mentioning
confidence: 86%
“…Although many of these studies have shown that tumors are stiffer than normal brain (Xu et al, 2007;Scholz et al, 2007Scholz et al, , 2005Chauvet et al, 2015), some have shown the opposite (Reiss- Zimmermann et al, 2015;Streitberger et al, 2014), and determination of stiffness differences between tumor grades has been inconclusive using this technique. Consistent with observations of stiffening of brain tumors, increased diffusion of water within a tumor, as measured by magnetic resonance imaging (MRI), is prognostic of poor outcome and is correlated with increased expression of ECM genes whose products are expected to stiffen a tissue (Pope et al, 2012(Pope et al, , 2009.…”
Section: Mechanical Properties Of Brain Tumor Subtypesmentioning
confidence: 99%
“…The biomechanical properties of the brain have been the subject of many recent studies related to hydrocephalus (1)(2)(3), traumatic brain injury (4)(5)(6), and the evaluation of stroke or intraoperative evaluation (7,8). Most biomechanical tests were carried out by invasive indentation experiments (9,10) to specifically measure the elasticity of cortical brain tissue.…”
Section: Introductionmentioning
confidence: 99%